PENGARUH COUNTRY OF ORIGIN, HARGA, DAN MEREK PADA NIAT BELI KONSUMEN PRODUK NETBOOK MEREK ACER, TOSHIBA, DAN ZYREX - , Farah Aprilia Faisal; , Ike Janita Dewi Dr, MBA, Ph. D, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
-